Triazine Calixarene as a Dual-Channel Chemosensor for the Reversible Detection of Cu2+ and I− Ions via Water Content Modulation - Fuyong Wu; Long Chen; Mei Yu; Liang Zhao; Lu Jiang; Tianzhu Shi; Ju Guo; Huayan Zheng; Ruixiao Wang; Mingrui Liao (Molecules)
Rationally designing and synthesizing chemosensors capable of simultaneously detecting both anions and cations via water content modulation is challenging. In this study, we synthesized and characterized a novel triazine calixarene derivative-based iodide and copper ion-selective fluorescent “turn-off” sensor. This dual-channeled fluorescent probe is able to recognize Cu2+ and I− ions simultaneously in aqueous systems. The fluorescent sensor s4 was synthesized by displacement reaction of acridine with 1, 3-bis (dichloro-mono-triazinoxy) benzene in acetonitrile. Mass spectrometry (MS), UV-vis, and fluorescence spectra were acquired to characterize the fluorescence response of s4 to different cations and anions, while infrared (IR) spectroscopy and isothermal titration calorimetry (ITC) were employed to study the underlying selectivity mechanism of s4 to Cu2+ and I−. In detail, s4 displayed extremely high sensitivity to Cu2+ with over 80% fluorescence decrement caused by the paramagnetic nature of Cu2+ in the aqueous media. The reversible fluorescence response to Cu2+ and the responses to Cu2+ in the solution of other potential interferent cations, such as Li+, Na+, K+, Ca2+, Cd2+, Zn2+, Sr2+, Ni2+, Co2+ were also investigated. Probe s4 also exhibited very good fluorescence selectivity to iodide ions under various anion (F−, Cl−, Br−, NO3−, HSO4−, ClO4−, PF6−, AcO−, H2PO4−) interferences. In addition to the fluorescent response to I−, s4 showed a highly selective naked-eye-detectable color change from colorless to yellow with the other tested anions.